Estudo sobre a Alimentação Mineral do algodoeiro I: marcha da absorpção do macronutrientes (Nota prévia) - Sarruge, J. R.; Gomes, L.; Haag, H. P.; Malavolta, E. (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1963)
Cotton (variety I. A. C. 11) was grown on a sandy soil under two treatments, namely: (1) NPK + lime and (2) no fertilizers. Three weeks after planting a systematic sampling of entire plants was done every other week. In the laboratory determinations of dry weight were made and afterwards the various plant partes were submitted to chemical analyses, nitrogen (N), phosphorus (P), potassium (K), calcium (Ca), magnesium (Mg), and sulfur (S) being determined. The aim of this work was to obtain information on the periods in which the absorption of the several macronutrients was more intense, this providing a clue for time of application of certain mineral fertilizers. Data obtained hereby allowed for the following main conclusions. The initial rate of growth of the cotton plant, judged by the determinations of dry weight, is rather slow. Seven weeks after planting and again five weeks two distinct periods of rapid growth take place. The uptake of macronutrients is rather small until the first flowers show up. From there on the absorption of minerals is intensified. From the time in which fruits are being formed to full maturity, the crop draws from the soil nearly 75 percent of the total amount of elements required to complet life cycle. This seams to point out the need for late dressings of fertilizers, particularly of those containing N and K. The following amounts of element in Kg/ha were absorbed by the fertilized plants: N - 83.2 P - 8.1 K - 65.5 Ca - 61.7 Mg - 12.8 and S - 33.2. The three major macronutrients, namely, N. P and K are exported as seed cotton in the following proportions with respect to the total amounts taken up by the entire crop: N - 1/3, P - 1/2 and K - 1/3.